2019
DOI: 10.1186/s40425-019-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antigen-engineered DC vaccines with or without IFNα to promote antitumor immunity in melanoma

Abstract: Background Cancer vaccines are designed to promote systemic antitumor immunity and tumor eradication. Cancer vaccination may be more efficacious in combination with additional interventions that may build on or amplify their effects. Methods Based on our previous clinical and in vitro studies, we designed an antigen-engineered DC vaccine trial to promote a polyclonal CD8 + and CD4 + T cell response against three shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 67 publications
2
30
0
3
Order By: Relevance
“…Because no significant differences were observed between arm 1 and arm 2 patients either in terms of clinical outcome or of Melan-A-specific immune responses, the immunological analyses were conducted cumulatively in arm 1 and arm 2 patients. Overall, our combination strategies enhanced the vaccine-specific CD8 + T cell frequencies in ∼69% of patients, but this rise did not correlate with the patient clinical outcome [similar to results obtained by Butterfield et al (44)]. On the contrary, the investigation of the quality of the immune response, carried out by means of a functional multiparameter assay (34), showed that the polyfunctionality of Melan-A-specific T cells is associated with disease control.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Because no significant differences were observed between arm 1 and arm 2 patients either in terms of clinical outcome or of Melan-A-specific immune responses, the immunological analyses were conducted cumulatively in arm 1 and arm 2 patients. Overall, our combination strategies enhanced the vaccine-specific CD8 + T cell frequencies in ∼69% of patients, but this rise did not correlate with the patient clinical outcome [similar to results obtained by Butterfield et al (44)]. On the contrary, the investigation of the quality of the immune response, carried out by means of a functional multiparameter assay (34), showed that the polyfunctionality of Melan-A-specific T cells is associated with disease control.…”
Section: Discussionsupporting
confidence: 75%
“…In a small melanoma vaccine trial testing the combination of high-dose IFN-α with autologous DC, transduced with three shared/nonmutated melanoma antigens, it was observed that among the 11 stage III/IV resected patients NED at baseline, seven recurred, and four remained NED (36.3 %) up to 3 years (3.7-37.5+ months). No indications of the OS of these patients are given in the article (44).…”
Section: Discussionmentioning
confidence: 99%
“…As recent work has illustrated differential efficacy of Prevnar vaccination in modulating the immune responses of adult mice to a post-influenza infection with a serotype 3 strain of Streptococcus pneumoniae, we chose to examine the impact of Pneumovax on these responses [30,40]. Given these findings, it would be plausible that other vaccines, designed with specific bacterial components, such as pneumococcal surface protein A (PspA) and pneumolysin (Ply) or liposomal encapsulation of polysaccharides (LEPS), may improve efficacy to post-influenza S. pneumoniae infection [31,[43][44][45]. Future work will need to evaluate if additional vaccine types can prove efficacious and further reduce inflammatory cytokine production while improving bacterial clearance post-influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial and patient samples A phase 1 single-site study was performed to evaluate the immunological effects of autologous monocyte-derived DCs transduced with tyrosinase, MART-1, and MAGE-A6 genes (by replication-defective AdV AdVTMM2) in 35 subjects with recurrent, unresectable stage III or IV melanoma (Butterfield et al, 2019). The clinical trial reported was fully approved by the University of Pittsburgh protocol review committee and institutional review board (PRO12010416, #UPCI09-021) and had Food and Drug Administration investigational new drug #15044 and NCT01622933 (clinical data finalized April 2018).…”
Section: Methodsmentioning
confidence: 99%